A educação Ciência-Tecnologia-Sociedade (CTS) no contexto dos anos iniciais do ensino fundamental - Oliveira, Ethel Silva de (2017)
This research is centered in the analysis of STS education in the early years of Elementary School, specifically focused on 4 th and 5th years. The investigation starts from the following issue: Although STS education is present in the curricular orientation for the teaching of Sciences, this is still centered in a traditional teaching, with an emphasis on scientific conceptualization, thus, it is important to investigate the comprehension and the actions promoted by the teachers for the incorporation of STS education in the early school years, with a view to mastering this traditional dimension. From this point, the research questions focus on: What is the insertion of STS education in the early years considering the Curricular Proposal of Sciences (CPS), the schoolbook and the conceptions of teachers from 4th and 5th years of Elementary School in public schools in Itacoatiara/Amazonas? Therefore, the general objective consists in: Analysing the introduction of STS education in the early years regarding the Curricular Proposal of Sciences, the schoolbook and the conceptions of teachers from 4th and 5th years of Elementary School in public schools in Itacoatiara/Amazonas. The methodology used founded on qualitative approach, in which documental research techniques were applied, semistructered interview and a workshop for result production, with a total of 18 participant teachers who worked in the 4th and 5th years at local schools in the city of Itacoatiara. The analysis of data was done from discursive textual analysis. In order to analyze the CPS, the discussions of teachers during the workshop and the schoolbook, we used the following categories: the content and approaches of social and environmental themes; evidence of technological knowledge; critical reflection of science and technology; participation and decision making. In order to analyze the STS conceptions of teachers, we started from the following categories of analysis: definition of Science and Technology; influence of Society in Science and Technology; influence of Science and Technology in Society. The results related to the CPS analysis point to some approximations with STS education, such as: formation for citizenship, adoption of Critical-Social Tendency of Content, articulation of STS elements in the general objective of Sciences field, and, about the distances, we identified a restricted focus of the content, mainly in the 1st to 3rd year block; it does not evidence an interdisciplinary and contextualized approach; besides presenting some contradictions upon prioritizing the fulfillment of labor market demands. The STS conceptions of teachers come close to a traditional conception of science and technology, but also a rupture, in part, when they conceive of the human side and the disastrous effects of science and technology. Regarding the schoolbook, the teachers identify some potentialities for STS education, such as: social and environmental approaches when dealing with deforestation, the impacts of industries, the risks and benefits of some human interventions in the environment, among others. Therefore, we defend the thesis that STS education is present in the teaching of Sciences in the early school years in a hybridised way by the traditional curricular conceptions and perspectives and STS comprehension through contextualization of scientific concepts.